Photoperiod effects on the growth stages of fall armyworm Spodoptera frugiperda (Lepidoptera: Noctuidae) under laboratory conditions - Putri, Redwika Clarissa; Megasari, Dita; Rahmadhini, Noni (Jurnal Ilmiah Pertanian, 2024)
Spodoptera frugiperda, commonly known as the fall armyworm, is a pest that attacks maize plants in Indonesia. Light is one of the crucial factors in the development of S. frugiperda. This study aims to observe and analyze the effects of different light exposure (photoperiod) on the duration of larval instars, pupal stage, and imago, as well as the body length and weight of S. frugiperda. The expected benefit of this research is to provide insights into how light influences the developmental stages of S. frugiperda under laboratory conditions. The test insects, S. frugiperda, were obtained from Agricultural Standardization Testing Center - Sweetener and Fiber Crops (BSIP-TAS) and were reared from the first instar larval stage, with a total of 56 individuals fed with young maize cobs. S. frugiperda undergoes complete metamorphosis, passing through egg, larval, pupal, and imago stages. The treatment with no light and 24 hours of darkness (0L:24D) resulted in the shortest duration for the larval, pupal, and imago stages, averaging 27.42 days, compared to other treatments. On the other hand, the 24L:0D treatment significantly affected body length and weight, showing distinct differences from other treatments (L: light; D: dark). The effect of light, using 238.89 lux illumination, was found to influence the development of S. frugiperda at each developmental stage.